Hoteliers’ Needs Analysis in a Five-Star Hotel: ESP Course Design Considerations - Xenia, Tia; Indriyani, Christina Eli (Universitas Pahlawan Tuanku Tambusai, 2025)
With the increasing demand for English proficiency in hospitality, ESP training becomes important to bridge the gap between communicative needs and current employee performance. Then, needs analysis serves as a foundation of ESP course design as the first phase to conduct a thorough identification of the learners’ needs to use the target language. This study investigated the English language needs in a five-star hotel in Jakarta involving 53 hoteliers from housekeeping, concierge, security, food and beverage, and engineering departments. The data were collected through questionnaires consisting of personal information, necessities, wants, lacks, and learning needs. The findings revealed that speaking and listening skills were the utmost used English skills in a five-star hotel in Jakarta. Consequently, the ESP course content should reflect the real workplace conditions. The hoteliers preferred interactive and communicative learning activities such as group discussion, watching videos, and games which foster experience sharing and problem-solving.